2022
DOI: 10.3389/fendo.2021.790591
|View full text |Cite
|
Sign up to set email alerts
|

hsa_circ_0111707 Is Associated With Risk of Stress-Related Type 2 Diabetes via Sponging miR-144-3p

Abstract: IntroductionChronic stress plays an important role in the development of type 2 diabetes (T2D). Circular RNAs (circRNAs) play significant roles in regulating the pathogenesis of diseases by regulating gene expression. The aim of the present study was to identify the association between hsa_circ_0111707 and stress-related T2D.MethodsThe present study was performed based on a three-part design. The association between hsa_circ_0111707 in peripheral blood mononuclear cells (PBMCs) and T2D and stress-related varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Depressive symptoms were associated with blunted and exaggerated cortisol responses to and recovery from stress, indicating the high risk of HPA axis dysregulation 46 . It was found that hsa_circ_0111707, mediated a negative correlation between scores of “demands at work” and “insecurity at work,” was associated with the risk of type 2 diabetes mellitus via sponging miR‐144‐3p 47 . According to the neuroplasticity hypothesis, glucocorticoids (GC) negatively affected neural development.…”
Section: Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depressive symptoms were associated with blunted and exaggerated cortisol responses to and recovery from stress, indicating the high risk of HPA axis dysregulation 46 . It was found that hsa_circ_0111707, mediated a negative correlation between scores of “demands at work” and “insecurity at work,” was associated with the risk of type 2 diabetes mellitus via sponging miR‐144‐3p 47 . According to the neuroplasticity hypothesis, glucocorticoids (GC) negatively affected neural development.…”
Section: Mechanismsmentioning
confidence: 99%
“… 46 It was found that hsa_circ_0111707, mediated a negative correlation between scores of “demands at work” and “insecurity at work,” was associated with the risk of type 2 diabetes mellitus via sponging miR‐144‐3p. 47 According to the neuroplasticity hypothesis, glucocorticoids (GC) negatively affected neural development. According to the neurogenesis hypothesis, GC negatively affected neural precursor cell proliferation.…”
Section: Mechanismsmentioning
confidence: 99%
“…CircHIPK3 and circ_0039480 are highly expressed in GDM and T2DM, respectively, and can be used as biomarkers for early diagnosis ( 124 , 125 ). Circ_0111707 was shown to increase the risk of stress-related T2DM by acting as a molecular sponge for miR-144-3p ( 126 ). Circ-Tulp4, which is downregulated in diabetic mouse islets, improves β-cell function by sponging miR-7222-3p and regulating the expression of cholesterol esterification-related genes, sterol O-acyltransferase 1 (SOAT1), and cyclin D1 signaling pathways to promote β-cell adaptation to lipotoxicity ( 127 ).…”
Section: Ncrnas In Diabetesmentioning
confidence: 99%